Analisis faktor keberhasilan menunjuk pada atlet petanque - Maliki, Osa; Suherman, Wawan Sundawan; Prasetyo, Yudik; Pradipta, Galih Dwi; Hartono, Ainun Rahma (Universitas Nusantara PGRI Kediri, 2022)
The research was conducted because of the various factors that influence the success of the pointing throw, so the evidence is needed for the factors that contribute to its success. This research aims to analyze the factors that give success in pointing throws. The method applied in this study uses descriptive correlational analysis to obtain a factor of determination on the results of the pointing throw. The subjects were 15 male athletes aged 15-17 years registered at FOPI Pati Regency with a total sampling technique. The results of data analysis show that the analysis of the physical component factors at pointing explains the formation of 3 components in the independent variable. This is shown in each component formed to have their respective contributions. Component 1 with member variables Eye-hand Coordination, Concentration, and Kinesthetic Perception has an effect of 42.937%, component 2 with member variables Arm muscle strength, wrist flexibility, and balancing have an effect of 19.403%, and component 3 with member variable Sleeve length has an influence of 13.508%. This study concludes that athletes with Eye-hand Coordination, Concentration, and Kinesthetic Perception will have a high pointing success rate on petanque.